2015
DOI: 10.1039/c4ta06001f
|View full text |Cite
|
Sign up to set email alerts
|

Na3V2(PO4)3 particles partly embedded in carbon nanofibers with superb kinetics for ultra-high power sodium ion batteries

Abstract: Na3V2(PO4)3 particles partly embedded in carbon nanofibers enabled fast electronic conduction as well as facile Na ion migration simultaneously. As a result, the composite showed excellent electrochemical properties as a cathode material for sodium ion batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(40 citation statements)
references
References 32 publications
2
38
0
Order By: Relevance
“…We have noted that both of these literatures (Table S1, Supporting Information) exhibit a cycle life of few thousands of cycles at ≥85% capacity retention in reality. Table S1 in the Supporting Information also provides the comparison of the present work with the recent literatures (since 2013) and evaluates the cycling stability at ≥85% capacity retention . These observations confirm that there is further scope to improve the rate capability and cycling performance by devising new nanostructured architectures for SVP/C composites.…”
Section: Introductionsupporting
confidence: 78%
“…We have noted that both of these literatures (Table S1, Supporting Information) exhibit a cycle life of few thousands of cycles at ≥85% capacity retention in reality. Table S1 in the Supporting Information also provides the comparison of the present work with the recent literatures (since 2013) and evaluates the cycling stability at ≥85% capacity retention . These observations confirm that there is further scope to improve the rate capability and cycling performance by devising new nanostructured architectures for SVP/C composites.…”
Section: Introductionsupporting
confidence: 78%
“…In this regard, various cathode materials, such as metal oxides, phosphates, and ferrocyanides have been investigated but their performances still fall short for EES applications. Na 3 V 2 (PO 4 ) 3 , with a fast Na + ‐transportable NASICON framework, has attracted ubiquitous attention as a promising cathode material for SIBs . Yamaki and co‐workers first reported a reversible capacity of 140 mA h g −1 of Na 3 V 2 (PO 4 ) 3 in the voltage range of 1.2–3.5 V .…”
mentioning
confidence: 99%
“…Recently, Jian et al introduced a carbon‐coating technique to improve the electric conductivity as well as cycling capability of Na 3 V 2 (PO 4 ) 3 . Promising results have ignited tremendous efforts to further advance the performance of Na 3 V 2 (PO 4 ) 3 by particle‐downsizing, which shortens transport distances of both Na ions and electrons, and surface‐coating of conductive carbon . Saravanan et al reported a porous Na 3 V 2 (PO 4 ) 3 /C composite characterized with an ultra‐long cycle life of 30 000 cycles at 40 C (4.7 A g −1 at a capacity of 61 mA h g −1 ) and a capacity retention of 50% .…”
mentioning
confidence: 99%
“…The particle size needs to be carefully designed for optimal chemical diffusion inside the particle (nanoparticle size scales are needed when a material is a poor conductor). In recently published reports, various kinds of carbon coatings are applied as a conducting network to improve electron transport and this may be in the form of carbon nanotubes/nanofibers/nanorods and/or graphene . Very recently, 3D interconnected conducting network strategies, which utilize a combination of different carbons have been investigated but only one publication on Na 3 V 2 (PO 4 ) 3 to date has explored the possibilities of a free‐standing electrode design …”
Section: Introductionmentioning
confidence: 99%